Pengenalan Nilai Tambah Melalui Pengolahan Dan Pemasara Saos Tomat Di SMK Agribisnis Dangau Datuk Bengkulu - Lina Asnamawati; Timbul Rasoki; Herry Novrianda; Dwi Kristanti; Ana Nurmalia (Universitas Lancang Kuning, 2021)
The Dangau Datuk Bengkulu Agribusiness Vocational Middle School has practicum facilities for cultivating various types of vegetables, one of which is tomatoes, which are sold directly at outlets provided to meet the daily needs of students. However, the characteristics of agricultural products are not durable,perishable, and rotten if they are not immediately sold. This problem has attracted the interest of proposers to help introduce value added analysis through processing tomatoes into tomato sauce which of course can lasta long time, have added value and high selling value. Students and some teachers have received value-added introduction training through sauce processing, operational management, training on determining the cost ofgoods sold (HPP). The ratio of added value from processing tomatoes into tomato sauce is obtained by 40% and the added value is obtained by subtracting the output value from other input prices and the raw materialprice of Rp. 6,666.67, meaning that every 1 kg of tomatoes costs Rp. creating added value of Rp. 6,666.67, - per Kg after being processed into tomato sauce.